2005
DOI: 10.1074/jbc.m409468200
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor Corepressors NCoR and SMRT Decrease Peroxisome Proliferator-activated Receptor γ Transcriptional Activity and Repress 3T3-L1 Adipogenesis

Abstract: The peroxisome proliferator-activated receptor ␥ (PPAR␥) is a central regulator of adipogenesis and recruits coactivator proteins in response to ligand. However, the role of another class of nuclear cofactors, the nuclear receptor corepressors, in modulating PPAR␥ transcriptional activity is less clear. Such corepressors include the nuclear receptor corepressor (NCoR) and the silencing mediator of retinoid and thyroid hormone receptors (SMRT). Our data suggest that PPAR␥ recruits SMRT and NCoR in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
179
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(198 citation statements)
references
References 43 publications
18
179
0
1
Order By: Relevance
“…83,84 Similarly, PPARg is bound to its target promoters in association with a number of repressors including HDACs and histone methyltransferases. 57,58,75,76,[80][81][82]97,99 At this stage, most adipogenic genes are characterized by bivalent histone marks, such as methylation of H3K27, H3K9 and H3K4. [35][36][37][38]50 Methylation of DNA is also found 120 as well as recruitment of a still inactive RNA Pol II.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…83,84 Similarly, PPARg is bound to its target promoters in association with a number of repressors including HDACs and histone methyltransferases. 57,58,75,76,[80][81][82]97,99 At this stage, most adipogenic genes are characterized by bivalent histone marks, such as methylation of H3K27, H3K9 and H3K4. [35][36][37][38]50 Methylation of DNA is also found 120 as well as recruitment of a still inactive RNA Pol II.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…96 In 3T3-L1 cells, addition of PPARg ligands breaks the PPARg/ NCoR complex and results in activation of PPARg transcriptional activity. 97,98 At the same time, binding to a ligand also enhances interaction of PPARg with CBP/p300, although this interaction may also happen in the absence of ligand. 94 Interestingly, a series of recent works have demonstrated that brown and white preadipocytes arise from different precursor cells, with brown preadipocytes being strikingly related to myoblasts.…”
mentioning
confidence: 99%
“…Among these are the PGC-1 coactivators that seem to play key roles in activating metabolic gene networks (18 -20). Although the importance of gene activation is well established, it is evident that gene repression is also a regulatory mechanism in adipogenesis (21). Recent studies have determined that gene repression is also a crucial factor in adipocyte function.…”
mentioning
confidence: 99%
“…6,7 Upon ligand binding, PPARg undergoes a conformational change and the corepressor complex is replaced by co-activators, including p300, the p160/steroid receptor co-activator (p160/SRC) family, the PPARg-binding protein, PPARg co-activator-1 (PGC-1), and the CREB-binding protein. 7,8 Many transcription …”
mentioning
confidence: 99%
“…6,7 Upon ligand binding, PPARg undergoes a conformational change and the corepressor complex is replaced by co-activators, including p300, the p160/steroid receptor co-activator (p160/SRC) family, the PPARg-binding protein, PPARg co-activator-1 (PGC-1), and the CREB-binding protein. 7,8 Many transcription factors and ligands are involved in expression and function of PPARg. Transcription factors of the CCAAT/enhancer-binding protein (C/EBP) family stimulate PPARg transcription by binding directly to the promoter of PPARg.…”
mentioning
confidence: 99%